Military and Water Governance Practices: A Theoretical Analysis of the Involvement of Indonesian National Armed Forces in the Citarum Harum Project in West Java, Indonesia - Mustabsyirotul Ummah Mustofa; Shafa Ghaisani Salsabila Brahmantika; Bima Riandy Tarigan (Journal of Asian Social Science Research, 2021)
The Citarum Harum project as stated in Presidential Regulation No. 15/2018 was created as a response to a report that Citarum is “the dirtiest river in the world”. It is said that the complexity of the management of the Citarum river involves the Indonesian National Armed Forces (TNI) as the program implementer. This military involvement is claimed as a non-war military operation to increase the Citarum Harum program's effectiveness. However, in the discourse of Water Governance, the military is hardly mentioned as an engaged stakeholder, especially in the framework of "governance" which emphasizes the democratic process controlled by civilians. This article seeks to explain what kind of regime can justify the claim of military involvement in water management as a vital public affair. A qualitative approach was used to achieve a comprehensive theoretical analysis in explaining this research problem. The findings indicate that military involvement in water governance is related to security issues, especially water security, and mainly in conflict areas. Meanwhile, in non-conflict areas, water governance places great importance on public and government participation in a very democratic process. Accordingly, the involvement of the TNI in the Citarum Harum program can be said as a practice that has deviated from the shared concept of water governance.